Uso de tecnologia da informação na agricultura familiar: Planilha para gestão de insumos - Affonso, Elaine Parra [UNESP]; Hashimoto, Cristina Toyoko [UNESP]; Sant'Ana, Ricardo César Gonçalves [UNESP] (University Library System, University of Pittsburgh, 2015)
Objective. To demonstrate how Information Technology through electronic spreadsheets may improve the administration of rural activities on farms, specifically within the context of family agriculture. Method. The literature on the use of Information Technology within the context of family agriculture was reviewed. Using the theoretical referential proposed by Community Informatics, the activities undertaken by the Digital Skills for Family Agriculture-CoDAF project were analyzed, especially the spreadsheet Input Stock Control, prepared on the information obtained from the interaction with rural producers. Their needs with regard to farm administration were consequently focused. Results. The spreadsheet Input Stock Control is consequently described and Information Technologýs contribution how it minimizes waste within the context of stock control is shown, coupled to lowering of costs and increase in the efficaciousness of the process. Conclusions. Although the farmer may have several impediments to access more advanced technologies and specific softwares, the use of the spreadsheet is a feasible choice due to its availability, mainly in open source versions, especially for family agriculture, and thus contributing towards the reduction of informational asymmetry.
Information Technology in family agriculture: Spreadsheets for the management of inputs
Keywords: Community informatics; Extension Projects; Family agriculture; Information Technology; Spreadsheets